Evaluasi Unjuk Kerja Boiler: Studi Kasus pada Pabrik Pulp dan Kertas PT. ABC - Nasution, Fikri Fahlevi; Khotimah, Nur; Sihombing, Tikkos; Martin, Awaludin (TURBO [Tulisan Riset Berbasis Online], 2024)
In process industries or power generation, boilers are one of the first components to consume energy. Moreover, poor combustion, heat transfer fouling, and improper operation and maintenance lead to a gradual decrease in efficiency. In addition, poor fuel and water quality cause boiler performance to decrease. As a result, efficiency testing helps determine how far the boiler efficiency deviates from the best efficiency level. A complete energy audit of the boiler was conducted at PT. ABC Pulp and Paper Mill with ASME (American Society for Mechanical Engineers) power test code, PTC 4.1. Direct method is an input-output method, and Indirect mehod is a method of heat loss that occurs in the boiler. The direct method shows an efficiency of 84.46% and the indirect method shows an efficiency of 78.73%. Based on direct and indirect methods showing a difference of 5.73%, it is reported that the total heat loss is 21.26% where the highest is in the dry flue gas of 14.88%, namely the incoming heat energy is carried away with dry flue gas.